“CHARACTERISTICS OF PAINTING SCHOOLS IN TEACHING PAINTING SCIENCE IN HIGHER EDUCATION INSTITUTIONS, DIFFERENCE FROM EACH OTHER, SIGNIFICANCE IN OUR NATIONAL CULTURE” - Ortikboy of girl Sattorova Sarvinozkhan (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, extensive information is provided about art schools in Uzbekistan and their uniqueness.